Facile hydrothermal synthesis and structural, optical, and morphological investigations on PVP assisted Fe doped CuO nanocomposites. (2016) - Kannaki, K.; Ramesh, P.S.; Geetha, D.
Abstract: Fe doped copper oxide (CuO) nanocomposites have been synthesized by hydrothermal method. The synthesized products have been characterized by XRD spectrometer, FT-IR, UV–Visible, PL, SEM/EDS spectroscopy, Atomic Force Microscopy (AFM), and TG–DTA analysis, respectively. XRD patterns show that the particle sizes are 16, 18, 21, and 17 nm, respectively for Fe (8, 10, 12, and 14%) doped CuO samples. FT-IR study confirms the presence of metal oxides within the wave number range 490 to 605 cm −1 . UV–Visible spectroscopy study shows the variation in direct band gaps and compared with XRD results. PL study reveals that the luminescence intensities of the as-synthesized samples increase with increasing doping material concentration due mainly to the increase of crystallinity. The porous aggregated nanocomposties, presence of Cu, Fe, and O elements have been confirmed by SEM /EDS analysis. AFM study confirms the formation cone shaped nanocomposites (10 nm), and are consistent with XRD results. Inorganic decomposition takes place in temperature range 276°C-362°C with an endothermic peak at 433°C indicates the formation of Fe (12%) doped CuO which was confirmed by TG–DTA analysis.